A prospective study of Mannheim peritonitis index as a prognostic scale in analysis of outcome in hollow viscus perforation - Ramesh, Abhilash Gautham; Ramesh, Kshama S. (International Surgery Journal, 2018)
Background: MPI as a prognostic index helps in analysis of prognosis in peritonitis in hollow viscus perforation. The factors that are considered in MPI index are routinely used in assessment of surgical patients, they are easily available, routinely performed, and helps in arrival at a prognosis in fast and effective way. Methods: A prospective survey of patients with acute generalized peritonitis due to hollow viscus perforation was carried out in general surgical wards of our institute during the period starting from January 2014 to December 2015. Study population consisted of 150 consecutive patients with performative peritonitis, which confirmed on emergency laparotomy. Results: The Mannheim peritonitis index emerged as a reliable marker for assessing the severity and prognosis of intra-abdominal infection with sensitivity and specificity comparable to APACHE II score which has been adopted as the gold standard by Surgical Infection Society. The score designed specifically for peritonitis, combines preoperative and operative data and is easy to apply. MPI scores were consistent with low scores among survivors and higher scores among non-survivors. Conclusions: MPI scores in the analysis were sharp predictor of mortality.